2017
DOI: 10.1371/journal.pone.0178137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of awareness & utilisation of clinical practise guideline for management of adult Dengue infection among Malaysia doctors

Abstract: Clinical Practice Guideline (CPG) provides evidence-based guidance for the management of Dengue Infection in adult patients. A cross sectional study was conducted to evaluate awareness and utilization of CPG among doctors in public or private hospitals and clinics in Malaysia. Doctors practicing only at hospital Medical and Emergency Departments were included, while private specialist clinics were excluded in this study. A multistage proportionate random sampling according to region (Central, Northern, Souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…Amongst health practitioners, it was shown that the level of awareness on Clinical Practice Guidelines (CPG) was higher amongst public health practitioners (99%) as compared to private practitioners (84%) [ 53 ]. Not surprisingly, the percentage of Medical Officer in private facilities utilising CPG was lower than those from public facilities (84% versus 98%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst health practitioners, it was shown that the level of awareness on Clinical Practice Guidelines (CPG) was higher amongst public health practitioners (99%) as compared to private practitioners (84%) [ 53 ]. Not surprisingly, the percentage of Medical Officer in private facilities utilising CPG was lower than those from public facilities (84% versus 98%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Out of 57 articles reviewed, 22 articles have piloted or pretested the questionnaire [ 24 , 29 , 34 , 36 , 38 , 41 , 48 , 50 , 53 , 57 , 63 , 65 , 66 , 67 , 68 , 71 , 72 , 73 , 75 , 77 , 78 , 79 ] before surveying. A total of 14 articles [ 26 , 30 , 31 , 33 , 35 , 37 , 42 , 43 , 47 , 51 , 54 , 62 , 74 , 80 ] were considered as having a high risk of bias on the questionnaire due to lack of evidence on validity and reliability (data not shown), among which two articles were adapted directly from the similar previous study, and 10 articles were a newly developed questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…They may be problematic, however, if patients requiring more tailored fluid regimes are not identified. Given previous survey evidence of good awareness and utilization of CPGs [13], this is concerning, as many participants reported having been unaware of how to calculate accurate fluid management. The reported high awareness of, and utilization of, ‘guidelines’ in surveys [13] may well refer to these fixed regime algorithms for fluid management.…”
Section: Discussionmentioning
confidence: 99%
“…CPGs also need to be routinely embedded in clinical practice, such that care can be co-ordinated across primary, secondary and tertiary levels and across departments within health care facilities. Quantitative survey evidence suggests a high degree of awareness and utilization of dengue management CPGs among Malaysian doctors, in both the public and private sectors (98 and 86% respectively) [13]. However, as in other settings, these self-reports of high utilization may not reflect actual practice.…”
Section: Introductionmentioning
confidence: 99%
“…Usage of Quick Reference is monitored by using feedback forms. Evaluation on users' awareness and adherence to selected CPGs such as the Dengue CPG (revised second edition) has also been conducted (12).…”
Section: Clinical Practice Guidelinesmentioning
confidence: 99%